Mother’s Influence On Cognitive Development: A Cultural Perspective. - Losike- Sedimo, Nonofo (Advances in Social Sciences Research Journal, 2018)
Parenting in most African cultures is practiced by both the nuclear family and the extended one. This is still a virtue in Setswana culture. This case study observed how a mother’s role in Botswana’ culture influence children’s cognitive development expressed in her daily practices. The objective was to establish how mother’s parenting style relates to cognitive development. The study analyses the experiences of a six-year-old Botswana boy against this background. The mothers’ role was isolated notwithstanding the fact that children grow up in multiple contexts of a given culture. Every culture is characterized, and distinguished from other cultures, by fundamental believes which are deep rooted and controls how children should feel, think, act, reflect, search for meaning, socialize and appropriately function as members of the society The study is guided by Bronfenbrenner’s Ecological theory which afforded the researcher to define which context will be considered for the study. It takes place in a rural undeveloped remote village in Botswana where a young boy of six years and his mother were studied under the five contexts of Bronfenbrenner’s theory. The research design was a case study. Results revealed that mothers and fathers share some childrearing attributes and effects, and differ in unique ways that influence different domains of child development. And that family members subscribed to unique conventions of culture and followed cultural scripts of raising children morally. It was concluded that cognitive development is influenced by the mother’s cultural roles. And that cultural contexts are multi-layered at home, in the neighbourhood, community and society. The results suggests that cognitive development is culture specific.